علاقة الاتصال غير اللفظي للأستاذ الجامعي بالدافعية للإنجاز لدى الطالب الجامعي - مسعودي, مروة; بالطاهر, النوي (جامعة الوادي - University of Eloued, 2022)
ملخص: هدفت إلى الكشف عن العلاقة بين الاتصال غير اللفظي للأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، واستخدمت في ذلك المنهج الوصفي الارتباطي، وطبقت على عينة تكونت من (100) طالب وطالبة بواقع (33) طالب و(67) طالبة، تم اختيارهم بالطريقة عشوائية، وبعد تطبيق الأدوات الخاصة بالدراسة، تم الحصول على النتائج التي تم معالجتها بواسطة معامل الارتباط بيرسون من خلال برنامج الحزمة الإحصائية للعلوم الاجتماعية . وقد أسفرت نتائج الدراسة على وجود علاقة ارتباطية ذات دلالة احصائية بين الاتصال غير اللفظي للأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، ووجود علاقة ارتباطية ذات دلالة احصائية بين ابتسامة الأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، ووجود علاقة ارتباطية ذات دلالة احصائية بين لغة جسد الأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، علاقة ارتباطية ذات دلالة احصائية بين المظهر المادي للأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، كذلك وجود علاقة ارتباطية ذات دلالة احصائية بين الاتصال البصري للأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي، مع وجود علاقة ارتباطية ذات دلالة احصائية بين صوت الأستاذ الجامعي والدافعية للإنجاز لدى الطالب الجامعي. Abstract: It aimed to reveal the relationship between the non-verbal communication of the university professor and the motivation for achievement of the university student, and in that connection, the descriptive approach was used, and it was applied to a sample consisting of (100) male and female students by (33) students and (67) students, who were chosen randomly, After applying the tools of the study, the results were obtained that were processed by the Pearson correlation coefficient through the Statistical Package for Social Sciences (SPSS) program. The results of the study resulted in a statistically significant correlational relationship between the non-verbal communication of the university professor and the motivation for achievement of the university student, and the existence of a statistically significant correlational relationship between the professor’s smile and the motivation for achievement of the university student, and the presence of a statistically significant correlational relationship between the university professor’s body language. The motivation forachievement of the university student is a statistically significant correlational relationship between the physical appearance of the university professor and the motivation for achievement of the university student, as well as the existence of a statistically significant correlational relationship between the visual contact of the university professor and the motivation for achievement of the university student, with the presence of a statistically significant correlational relationship between the professor’s voice University and achievement motivation for university students.
دراسة ميدانية بجامعة الوادي
مقال
Keywords: الاتصال غير اللفظي ; الدافعية للإنجاز; Nonverbal communication; Motivation for achievement